Strong Consistency of the Least-Squares Estimator in Simple Regression Models with Stochastic Regressors - Norbert Christopeit; Michael Massmann (Tinbergen Institute, 2012)
Strong consistency of least squares estimators of the slope parameter in simple linear regression models is established for predetermined stochastic regressors. The main result covers a class of models which falls outside the applicability of what is presently available in the literature. An application to the identification of economic models with adaptive learning is discussed.
urn:NBN:nl:ui:31-1871/38765
Keywords: C13; C22; D83; D84; 330; linear regression; least-squares; consistency; stochastic regressors; adaptive learning; decreasing gain; Regression; Stochastischer Prozess; Prognoseverfahren; Methode der kleinsten Quadrate